2018
DOI: 10.7224/1537-2073.2016-106
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Evaluation of Cognitive Fatigue on a Task of Sustained Attention in Early Relapsing-Remitting Multiple Sclerosis

Abstract: Although individuals with MS continue to be vulnerable to cognitive fatigue at follow-up, severity does not seem to increase with time. Cognitive fatigue may be a more sensitive marker of cognitive impairment than overall task performance in those with early-phase RRMS, which has important implications given that clinically only task performance is typically assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 33 publications
1
39
2
1
Order By: Relevance
“…A corollary of this interpretation is that MS patients probably need to increase their engagement of alerting and orienting mechanisms to improve their reaction in each trial to relocate their attentional focus as fast as possible. The maintenance of this strategy to compensate for the deficit is probably the cause of cognitive fatigue observed in some cases among MS patients during sustained attention tasks 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…A corollary of this interpretation is that MS patients probably need to increase their engagement of alerting and orienting mechanisms to improve their reaction in each trial to relocate their attentional focus as fast as possible. The maintenance of this strategy to compensate for the deficit is probably the cause of cognitive fatigue observed in some cases among MS patients during sustained attention tasks 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is corroborated by previous findings that indicated people with lower education to be less used to applying cognitive strategies [55] resulting in being more prone to cognitive fatigue. However, the association between fatigue and cognitive performance related to attention functioning, assessed with PASAT‐3, was not significant, highlighting how cognitive fatigue is independent of fatigability [56–58] induced by the task [59]. Moreover, fatigue appears to be independent of cognitive dysfunction; indeed, although it can occur at any stage of the disease, it is often already present at onset in patients without cognitive impairment and with low disability [60].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing drive to examine cognitive performance fatigability in MS has demonstrated that people with MS are vulnerable to cognitive performance change (Berard et al , 2018, Cehelyk et al , 2018, Claros-Salinas et al , 2013, Wolkorte et al , 2015. However, similarly to our understanding of perceived fatigue, the factors influencing cognitive performance change remain unclear.…”
Section: Introductionmentioning
confidence: 99%